A biofilm microenvironment-responsive one-for-all bactericidal nanoplatform for photothermal-augmented multimodal synergistic therapy of pathogenic bacterial biofilm infection. Issue 38 (3rd September 2022) - Yang, Ke; Hai, Luo; Wang, Zefeng; Li, Huan; Yi, Wenhua; Luo, Yuze; Li, Junqin; Deng, Le; He, Dinggeng
Abstract : We rationally construct a biofilm microenvironment-responsive bactericidal nanoplatform (ZnPMp) consisting of ZnO core, a Fe 3+ -doped polydopamine coating and methylene blue (MB) payload for combined CT/CDT/PTT/PDT multi-mode antibacterial therapy. Abstract : Multimodal synergistic bactericidal agents display great potential for fighting biofilm infections. However, the rational design of biofilm microenvironment (BME)-activatable therapeutic agents with excellent specificities, effective eradications and minimal side effects remains a great challenge. Herein, we show a BME-responsive one-for-all bactericidal nanoplatform consisting of Fe 3+ -doped polydopamine (Fe/PDA)-capped ZnO nanoparticles with a successive assembly of methylene blue (MB) and poly(ethylene glycol) (PEG). In an acidic BME (pH 5.5), the constructed nanoagent (ZnPMp) can realize the co-delivery of dual metal ions (Zn 2+ and Fe 3+ ) and MB, and the latter shows an activated photodynamic antibacterial activity when irradiated with 635 nm laser. Zn 2+ produced from acid-sensitive dissolution of ZnO is an effective chemical antibacterial agent. Additionally, the released Fe 3+ is reduced to Fe 2+ by glutathione (GSH) overexpressed in the BME to generate Fe 2+ /Fe 3+ redox couples, which exhibit Fenton catalytic activity to convert endogenous H2 O2 to hydroxyl radicals (˙OH) for chemodynamic sterilization and GSH depletion ability to improve ˙OH-induced oxidative damage. Interestingly, the hyperthermia caused by the Fe/PDA layer assisted with 808 nm laser can damage directly bacterial cells, accelerate the release of Zn 2+, Fe 3+ and MB, and promote the catalytic activity of Fe 2+ /Fe 3+ redox couples for photothermal-augmented multimodal antibiofilm therapy. With the help of dual lasers, ZnPMp displays the broad-spectrum antibacterial effect, inhibits effectively the formation of biofilms, and more importantly eliminates bacteria deep in mature biofilms. In addition, ZnPMp can be used to treat biofilm-related infections in vivo with excellent therapeutic performance and minimal toxicity. Overall, the developed ZnPMp may serve as a potential nano-antibacterial agent for intensive anti-infective therapy.